The decision to purchase Nasi Krawu Bu Azza in terms of brand, price, product quality and packaging - Fikri, Ahmad Kanzul; Arief, Mohammad (Eco-Entrepreneur, 2023)
The background of this research is the increasingly tight competition in the Nasi Krawu business which has an impact on decreasing the number of visitors to Nasi Krawu Bu Azza. This study aims to determine the effect of brand, price, product quality and packaging on purchasing decisions for Nasi Krawu Bu Azza in Gresik. This study uses quantitative methods and sampling in this study uses accidental sampling and is analyzed using multiple linear regression analysis. The results of this study indicate that the variables Price, Product Quality and Packaging partially have a positive and significant effect on purchasing decisions, except for the brand variable.